Teaching of Angle of Elevation by Integrating Angle Measurement in Ancient Egyptian Mathematics - Juquiana, Steffan-Mae; Carlo Padua, John; Ilao, Herminia; Simangan, Joan; Esteban Elipane, Levi (International Journal of Engineering and Technology, 2018)
The aim of this study is to stimulate reflections and determine the effects of teaching mathematics by integrating its history through Lesson Study. Lesson Study was utilized as a process to delve into the possible outcomes of incorporating history of mathematics in teaching angle of elevation to 15 freshmen college students taking BS Air Transportation. The researchers followed the three steps in conducting a Lesson Study; planning, implementing, and conducting the post-lesson discussion. The implementation of the lesson and the post-lesson discussion were video and audio recorded which later on transcribed. Three issues in attaining the objectives of the lesson were identified: (1) Being Able to Set-up the Condition and Being Clear with the Instructions (2) Being Realistic with Examples, and (3) Importance of Processing Methodologies, which greatly play an important share on maximizing the learning process and studentsâ€™ success. Furthermore, feedbacks from the observers and students suggests that using history of mathematics enhanced studentsâ€™ curiosity about the significance of the lesson in real life. This study may contribute to the advancements of innovative teaching strategies to the rest of educators and researchers.Â Â